The Penguin book of erotic stories by women (Viking, 1995)
An international collection spanning one hundred years. From Elizabeth Cook's Billets Doux, on a woman's imaginative punishment for a man's infidelity, to Yuan Ch'iung Ch'iung's A Lover's Ear, on the erotic experience of cleaning your loved one's ear.